In situ Measurements and Model Estimates of NO3 and NH4 Uptake by Different Phytoplankton Size Fractions in the Southern Benguela Upwelling System - Atkins, J. Ffion; Moloney, Coleen L.; Probyn, Trevor A.; Bernard, Stewart (Frontiers in Marine Science, 2016)
Bulk measurements can be made of phytoplankton standing stocks on a quasi-synoptic scale but it is more difficult to measure rates of production and nutrient uptake. We present a method to estimate nitrogen uptake rates in productive coastal environments. We use observed phytoplankton cell size distributions and ambient nitrogen concentrations to calculate uptake rates of nitrate, ammonium and total nitrogen by different size fractions of diverse phytoplankton communities in a coastal upwelling system. The data are disaggregated into size categories, uptake rates are calculated and these uptake rates are reaggregated to obtain bulk estimates. The calculations are applied to 72 natural assemblages for which nitrogen uptake rates and particle size distributions were measured in situ. The calculated values of total N uptake integrated across all size classes are similar to those of in situ bulk measurements (N slope=0.90), (NH$_{4}$ slope=0.96) indicating dependence of NH$_{4}$ and total N uptake on ambient N concentrations and cell size distributions of the phytoplankton assemblages. NO$_{3}$ uptake was less well explained by cell size and ambient concentrations, but regressions between measured and estimated rates were still significant. The results suggest that net nitrogen dynamics can be quantified at an assemblage scale using size dependencies of Michaelis-Menten uptake parameters. These methods can be applied to particle size distributions that have been routinely measured in eutrophic systems to estimate and subsequently analyse variability in nitrogen uptake.